2004
DOI: 10.1016/j.clpt.2004.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and oral alfentanil as in vivo probes for hepatic and first-pass cytochrome P450 3A activity: Noninvasive assessment by use of pupillary miosis

Abstract: ALF and MDZ have similar intestinal extraction but low and intermediate hepatic extraction, respectively. Systemic and oral clearances of ALF are excellent in vivo probes for hepatic and first-pass CYP3A activities and drug interactions. Miosis was an acceptable surrogate for plasma ALF. ALF miosis may be a suitable noninvasive in vivo probe for both hepatic and first-pass CYP3A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(146 citation statements)
references
References 56 publications
(178 reference statements)
9
135
0
2
Order By: Relevance
“…When midazolam was administrated intravenously, the average induction of midazolam clearance by rifampicin was reported to be 2-fold (Floyd et al, 2003;Gorski et al, 2004;Kharasch et al, 2004;Yu et al, 2004). In the study by Gorski et al (2004), the range of induction of midazolam clearance by rifampicin was reported to be between 1.4-and 7.4-fold.…”
Section: Discussionmentioning
confidence: 92%
“…When midazolam was administrated intravenously, the average induction of midazolam clearance by rifampicin was reported to be 2-fold (Floyd et al, 2003;Gorski et al, 2004;Kharasch et al, 2004;Yu et al, 2004). In the study by Gorski et al (2004), the range of induction of midazolam clearance by rifampicin was reported to be between 1.4-and 7.4-fold.…”
Section: Discussionmentioning
confidence: 92%
“…Hepatic CYP3A activity was evaluated on day 2 using i.v. alfentanil as an in vivo probe (Kharasch et al, 2004b(Kharasch et al, , 2008b(Kharasch et al, , 2009a(Kharasch et al, ,b, 2011a(Kharasch et al, ,b, 2012a. Subjects received ondansetron followed 30 minutes later by alfentanil bolus (15 and 5 mg/kg at control and ritonavir-lopinavir sessions, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…First-pass CYP3A activity and intestinal P-gp (and other transporters) activity were evaluated on day 1 using oral alfentanil and fexofenadine as in vivo probes (Kharasch et al, 2004b(Kharasch et al, , 2005(Kharasch et al, , 2008b(Kharasch et al, , 2009a(Kharasch et al, ,b, 2011a(Kharasch et al, ,b, 2012a. Subjects received ondansetron (4 mg i.v.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B, dose of RIF, 600 mg q.d. The observed DDI data were the means of 9 or 10 subjects (Backman et al, 1996(Backman et al, , 1998Kharasch et al, 2004) for RIF dosed for 5 days, 8 subjects (Link et al, 2008) for RIF dosed for 6 days, 14 subjects (Gorski et al, 2003) for RIF dosed for 7 days, 19 subjects (Chung et al, 2006) for RIF dosed for 9 days, 16 subjects (Adams et al, 2005) for RIF dosed for 14 days, and 57 subjects (Floyd et al, 2003) (Fig. 3, A-C).…”
Section: Prediction Of Multiple Dose Pharmacokinetics Of Cyp3a4mentioning
confidence: 99%